Intramuscular Hemangioma in Lip Treated with Sclerotherapy and Surgery - Vanessa A. Silva; Nádia L. Lima; Ana Terezinha M. Mesquita; Esmeralda Maria da Silveira; Flaviana D. Verli; João Luiz de Miranda; Cássio Roberto R. Santos; Sandra A. Marinho (Case Reports in Dentistry)
Intramuscular hemangioma is a relatively rare, benign tumor of vascular origin, accounting for less than 1% of all hemangiomas. This paper reports a case of a 48-year-old female patient with intramuscular hemangioma in the upper lip, treated with sclerotherapy and subsequent complementary surgery.